Insight into loading, release, and anticancer activities of the methanol hybridized glauconite nano-sheets as a potential carrier of cisplatin: equilibrium and release kinetics - Alfassam, Haifa E.; Nasser, Nourhan; Othman, Sarah I.; Alharbi, Hanan M.; Alenazi, Noof A.; Rudyani, Hassan A.; Allam, Ahmed A.; Al Zoubi, Wail; Abukhadra, Mostafa R. (Frontiers in Chemistry, 2025)
Advanced silicate nano-sheets as exfoliated and separated layers were developed from natural glauconite and hybridized with methanol, producing a methoxy exfoliated structure (Mth/EXGL). The structure was assessed as an enhanced carrier of the cisplatin drug (CSPN) with significant loading, release, and cytotoxicity properties. The methoxy form of exfoliated glauconite showed better loading properties (327.7 mg/g) than the exfoliated sample (202.4 mg/g) as well as the raw sample (119.3 mg/g). This enhancement was assigned to the incorporated active loading centers after the methanol hybridization step, which is in agreement with the steric studies and determined active site density (Nm = 45.5 mg/g (Mth/EXGL), 38.4 mg/g (EXGL), and 26.3 mg/g (glauconite). Moreover, each site across the interface of Mth/EXGL has the capacity to be loaded with 8 CSPN molecules, donating multi-molecular mechanisms and their loading in vertical orientation. The CSPN loading energy value (<8 kJ/mol) into Mth/EXGL reflected the dominant impact of the physical mechanisms, including electrostatic attractions and hydrogen bonding. The recognized release profile demonstrates continuous and controlled behavior that can extend up to 110 h at pH 7.4 and 170 h at pH 5.5. This releasing behavior is regulated by two main processes (diffusion and erosion) based on the release kinetic findings. Also, Mth/EXGL as a carrier of CSPN induces its cytotoxic effect on human cervical epithelial tumors (HeLa) (0.65% cell viability) as compared to the free form of CSPN (6.6% cell viability). The Mth/EXGL is recommended as a delivery system for CSPN considering its determined loading, release, and cytotoxicity properties.